Role of plastoglobules in metabolite repair in the tocopherol redox cycle - Eugeni Piller, Lucia; Glauser, Gaétan; Kessler, Felix; Besagni, Céline (Frontiers in Plant Science, 2014)
Plants are exposed to ever changing light environments and continuously forced to adapt. Excessive light intensity leads to the production of reactive oxygen species that can have deleterious effects on photosystems and thylakoid membranes. To limit damage, plants increase the production of membrane soluble antioxidants such as tocopherols. Here, untargeted lipidomics after high light treatment showed that among hundreds of lipid compounds alpha-tocopherol is the most strongly induced, underscoring its importance as an antioxidant. As part of the antioxidant mechanism, α-tocopherol undergoes a redox cycle involving oxidative opening of the chromanol ring. The only enzyme currently known to participate in the cycle is tocopherol cyclase (VTE1, At4g32770), that re-introduces the chromanol ring of α-tocopherol. By mutant analysis, we identified the NAD(P)H-dependent quinone oxidoreductase (NDC1, At5g08740) as a second enzyme implicated in this cycle. NDC1 presumably acts through the reduction of quinone intermediates preceding cyclization by VTE1. Exposure to high light also triggered far-ranging changes in prenylquinone composition that we dissect herein using null mutants and lines overexpressing the VTE1 and NDC1 enzymes.